Birdwatchers evoke longer escape distances than pedestrians in some African birds. Issue 1 (2nd January 2019) - Radkovic, Anna Z.; Van Dongen, Wouter F. D.; Kirao, Lennox; Guay, Patrick-Jean; Weston, Michael A.
ABSTRACT: Birdwatching attracts many bird enthusiasts to developing economies, and is generally considered an innocuous activity with few impacts on birds. Birdwatchers generally attempt to remain as inconspicuous as possible when approaching birds, and their movement is different to that of other users of natural areas. However, how birds respond to birdwatchers, compared with humans conducting other activities, has rarely been tested. We randomly conducted pedestrian (i.e. consistent walking) and 'birdwatcher' (i.e. stops each 5 paces to view a bird through binoculars) approaches to 20 East African bird species and measured their escape responses. Four species ( α = 0.05; 7 if α = 0.10) exhibited significantly and substantially (1.7–2.2 times) longer flight-initiation distances (FIDs) to birdwatcher approaches. No differences in escape mode (flying versus on foot) were evident. While birdwatching appears no more disturbing per episode than walking for most species, some species evidently judge birdwatchers as more threatening. This information has important implications for management strategies focused on minimizing birdwatching impacts in natural areas.